Upaya Guru Pendidikan Agama Islam Dalam Meningkatkan Motivasi Belajar Siswa di Mts Al-Hikmah Sidang - Aidil Fitri; Irwansyah; Andre; Rangga Lawe; Putra, Purniadi (Jurnal Ilmu Sosial dan Humaniora, 2024)
Teachers are professional educators who have an important role in teaching, guiding, directing, training and assessing. In line with the development of the meaning of learning from teacher-oriented learning to student-oriented learning, the role of a teacher in the learning process has also shifted, one of the teacher's roles is as a motivator. Thus, the role of the teacher apart from being an educator and teacher also plays a role as a motivator for his students. Because in this way, students will not experience a saturation point and in the end students' interest and motivation in learning will continue to increase. Motivation can be said to be the overall driving force within students which creates, ensures continuity and provides direction to learning activities, so that it is hoped that goals can be achieved. This research will examine the efforts made by teachers in the field of Islamic religion to increase student learning motivation. This research is field research using descriptive analytical research methods, namely by describing and interpreting objects. Data collection techniques through observation, interviews with teachers, and documentation. Based on the results of the data analysis that has been carried out, the author concludes that the way to increase student learning motivation at MTs Al-Hikmah Sidang is to give advice, provide opportunities to show themselves, create an atmosphere of healthy competition.